Enhancing poultry industry competitiveness: consumer perspective on chicken meat quality based on sensory characteristics - Imran, Siti Nasihah; Kamarulzaman, Nitty Hirawaty; Abd Latif, Ismail; Mohd Nawi, Nolila (Routledge, 2014)
The increasing demand for chicken meat has caused producers to increase their productivity through enhanced production techniques. Further increase in demand for quality meat products has been predicted in the country. This study seeks to investigate factors that influence consumer perception toward chicken meat quality. Face-to-face interviews were carried out with 569 consumers at selected shopping malls located in Klang Valley areas. The majority of the respondents perceived quality as an important criterion for buying decisions. The finding revealed that nine factors have influenced consumer perception on meat quality, namely color, size, springiness, chicken aroma, fatty/oily taste, sweetness, visible fat, tenderness, and fibrousness. Among these factors, tenderness was found to be the most important criterion that influenced consumer preference toward chicken meat quality during buying decisions. Good production practices and proper marketing strategies are among recommendations to poultry industry players toward fulfilling consumer demand for good quality chicken meat.